Epitaxial Growth of 2D Materials on High‐Index Substrate Surfaces. (3rd May 2021) - Zhang, Leining; Peng, Peng; Ding, Feng
Abstract: Recently, the successful synthesis of wafer‐scale single‐crystal graphene, hexagonal boron nitride (hBN), and MoS2 on transition metal surfaces with step edges boosted the research interests in synthesizing wafer‐scale 2D single crystals on high‐index substrate surfaces. Here, using hBN growth on high‐index Cu surfaces as an example, a systematic theoretical study to understand the epitaxial growth of 2D materials on various high‐index surfaces is performed. It is revealed that hBN orientation on a high‐index surface is highly dependent on the alignment of the step edges of the surface as well as the surface roughness. On an ideal high‐index surface, well‐aligned hBN islands can be easily achieved, whereas curved step edges on a rough surface can lead to the alignment of hBN along with different directions. This study shows that high‐index surfaces with a large step density are robust for templating the epitaxial growth of 2D single crystals due to their large tolerance for surface roughness and provides a general guideline for the epitaxial growth of various 2D single crystals. Abstract : To epitaxially grow large area single crystals of hBN and other 2D materials with lower symmetries, using a high‐index substrate is highly favorable. The above figure illustrates the alignments of hBN islands on various Cu surfaces, from which we can clearly see that the unidirectional alignment of hBN islands can be achieved on various high‐index Cu surfaces.